Termination of Prosecution by Public Prosecutor in Corruption Crime in Indonesia: A Comparison with Various Countries - Mantri, Bagus Hanindyo; ., Hartiwingsih; Rustamaji, Muhammad (Journal of Ecohumanism, 2025)
This study seeks to elucidate the methodologies and regulatory frameworks surrounding public prosecutors’ cessation of prosecution in corruption within Indonesia. The author subsequently draws comparisons with various nations, specifically the Netherlands, France, and Denmark. This study employs a normative legal framework, utilising a statutory approach, a conceptual approach, and a comparative legal methodology. This study’s findings indicate that public prosecutors’ cessation of prosecution in corruption in Indonesia is grounded in legal principles, one of which applies to offenders whose actions result in minimal financial detriment to the state. This aligns with the powers granted to public prosecutors in the Netherlands, France, and Denmark. In these jurisdictions, the public prosecutor can exercise prosecutorial discretion when it is deemed that a case lacks merit for court proceedings. For instance, this may occur when the expenses of managing the case exceed the losses incurred, mainly if those losses have already been compensated.